PHYTOCHEMICAL STUDY OF THE ESSENTIAL OIL OF PELARGONIUM ROSEUM BY GAS CHROMATOGRAPHIC METHOD - Carmen Galea; Dorin Ioan Cocoș; Norina Consuela Forna; Mariana Păcurar; Earar Kamel (Romanian Society of Oral Rehabilitation, 2024)
The study presents a detailed investigation of the essential oil obtained by distilling the stems of Pelargonium roseum, also known as geranium oil, cultivated at the bio-farm of the Faculty of Pharmacy in Galați, Romania. Interest in this study was sparked by the potential applications of the oil in interdisciplinary fields such as pharmacy and dentistry, considering the diversity and varying concentrations of its phytoconstituents. The research is notable for focusing on the compositional analysis of oils obtained during the pandemic years 2020, 2021, and 2022, periods marked by the global SARS-CoV-2 health crisis. The chosen methodology for the detailed analysis of the oil components includes gas chromatography coupled with mass spectrometry, using the Adams protocol for precise identification and quantification. The mass spectra obtained were compared with those from the Wiley standard library, facilitating a rigorous evaluation of the chemical profiles. The main findings indicate a predominance of monoterpene alcohols - citronellol, geraniol, and linalool - present in free or esterified forms. Citronellol, in particular, stands out due to its high concentrations, conferring notable antibacterial and antifungal properties to the oil, superior to other volatile oils analyzed. This feature recommends it as a promising candidate for medical applications, especially in dentistry. Based on the results, the study proposes an in-depth exploration of the antibacterial efficacy of geranium oil, aiming at the development of new pharmaceutical preparations with controlled release. These preparations could enhance current treatments by offering efficient natural alternatives for preventing and combating bacterial and fungal infections in dental practice. Thus, the study emphasizes the importance of continuing research in this field, highlighting the valuable potential of essential oils in modern medical applications.